Omijać prawdę jak dziury w drodze: o relatywistycznym intencjonalizmie Stanleya Fisha - Kalaga, Tomasz (Er(r)go. Teoria - Literatura - Kultura, 2006)
Tomasz Kalaga Dodging the Truth like Stray Bullets: Stanley Fish's Relativist Intentionalism. The article discusses of the notion of truth in the context of Stanley Fish's reader-response criticism. The initial comparison of Fish's theory with several contemporary philosophical paradigms paves way for the argumentation in favour of acknowledging the subversive presence of the otherwise clandestine concept of truth in Fish's writings. Focusing on the ideas of meaning and rhetoric, the subsequent juxtaposition of Fish's ideas with the hermeneutic thought attempts to uncover this implied presence and outline possible consequences for the concepts of interpretation and textual stability.